Contact allergies to dental materials in patients - Forkel, Susann; Schubert, Steffen; Corvin, Lisa; Heine, Arndt Guido; Lang, Claudia C.; Oppel, Eva Maria; Pfoehler, Claudia; Treudler, Regina; Bauer, Andrea; Sulk, Mathias; Kraenke, Birger; Schäkel, Knut; et al. (British journal of dermatology, 2024)
Contact allergy to dental materials is a rare condition. Affected patients with contact allergy are predominantly middle-aged or older women. Sensitization is caused primarily by metals, additives and (meth)acrylates. Background Concerns regarding contact allergies and intolerance reactions to dental materials are widespread among patients. Development of novel dental materials and less frequent amalgam use may alter sensitization profiles in patients with possible contact allergy.Objectives To analyse current sensitization patterns to dental materials in patients with suspected contact allergy.Methods This retrospective, multicentre analysis from the Information Network of Departments of Dermatology (IVDK) selected participants from 169 834 people tested in 2005-2019 and registered with (i) an affected area of 'mouth' (and 'lips'/'perioral'), (ii) with the dental material in question belonging to one of three groups (dental filling materials, oral implants or dentures or equivalents) and (iii) with patch-testing done in parallel with the German baseline series, (dental) metal series and dental technician series.Results A total of 2730 of 169 834 tested patients met the inclusion criteria. The patients were predominantly women (81.2%) aged >= 40 years (92.8%). The sensitization rates with confirmed allergic contact stomatitis in women (n = 444) were highest for metals (nickel 28.6%, palladium 21.4%, amalgam 10.9%), (meth)acrylates [2-hydroxyethyl methacrylate (HEMA) 4.8%] and the substances propolis (6.8%) and 'balsam of Peru' (11.4%). The most relevant acrylates were HEMA, 2-hydroxypropyl methacrylate, methyl methacrylate, ethylene glycol dimethacrylate and pentaerythritol triacrylate. Few men were diagnosed with allergic contact stomatitis (n = 68); sensitization rates in men were highest for propolis (14.9%) and amalgam (13.6%).Conclusions Allergic contact stomatitis to dental materials is rare. Patch testing should not only focus on metals such as nickel, palladium, amalgam and gold, but also (meth)acrylates and the natural substances propolis and 'balsam of Peru'.
Online veröffentlicht: 20 December 2023
Gesehen am 06.02.2025